Factors affecting community participation in the waste bank in sukoharjo regency: Implications for circular economy - Dara Sari Lusia; Marwanti Sri; Barokah Umi (E3S Web of Conferences)
Waste management is a challenge in various regions, such as Sukoharjo Regency, where waste generation reached 361.92 tons per day in 2022. One approach to addressing this issue is the establishment of waste banks. Waste banks engage in activities such as buying, selling, and processing waste, which are all part of the circular economy concept. The success of waste bank operations depends on community participation. This study aims to identify the factors influencing community participation in waste bank programs and to determine the relationship between participation and the circular economy. This research used binary logistic regression analysis and causal loop diagram (CLD) modeling. The results indicate that the variables of knowledge and socialization related to waste significantly affect community participation. The CLD model illustrates that the relationship between socialization and knowledge is mutually “reinforcing,” while the relationship between socialization, knowledge, participation, and the circular economy is “balancing.” These findings highlight the importance of improving waste-related knowledge through regular and effective socialization efforts. The increase in participation in waste bank activities will boost the amount of waste processed and have the potential to be integrated with other sectors.